Comparative Criminal Law Policy Positives With Foreign Countries In The Criminal Law Prosecuting Perpetrators Of Criminal Acts Of A Child In Indonesia - Tutut Suciati Handayani (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
In this study the issues to be discussed are: the policy positive criminal law in the prosecution of perpetrators of criminal acts of a child, criminal law policy of foreign countries in the prosecution of perpetrators of criminal acts of children and the barriers prosecutor in carrying out the task of prosecuting perpetrators of criminal acts of child and how the efforts countermeasures. The research method that will be used is the juridical sociological approach. In order to obtain primary data and secondary data that is accurate to the writing of this study, the data collection by means of a literature study to find materials relating to the principles and rules of law relating to criminal procedure law and the criminal justice system of children. Based on the results of this research is still fragmented between the investigator and the prosecutor so that ultimately the criminal justice system is not optimal child be a solution to cope with the child as a criminal. The issue of children as criminals not only be approached only by using purely legal approach, but also must use the instrument of social and economic approaches. That in conducting the prosecution against children, public prosecutors are often encountered problems due to its law system, the apparatus structure and legal culture. therefore it is necessary for the reconstruction of the criminal justice system of Indonesia, so it can be used as a reference for events that are special laws such as the juvenile justice system.Keywords: Comparative, Policy, Criminal Law.